Identifying governance challenges in scaling biofortification programs and the potential of training: a case study of Uganda - Alioma, Richard; Zeller, Manfred; Birner, Regina; Bosch, Christine; Muayahoto, Bho (Frontiers in Sustainable Food Systems, 2025)
IntroductionBiofortification initiatives can significantly help reduce micronutrient deficiencies in developing countries. However, when hidden hunger affects a large segment of the population, large-scale implementation is necessary to achieve the desired results. We aimed to identify governance challenges in biofortification, and potential remedies based on a conceptual framework that considers low demand and the invisible nature of micronutrient traits in crops.MethodsUsing process net maps and quantitative methods, this paper explores how farmer training can address governance issues.ResultsResults show that, in addition to common agricultural marketing issues, sweet potato vine multipliers struggle with vine supply, value chain actors adulterate iron beans, and consumers are hesitant to pay higher prices for biofortified crops. These problems may result from information asymmetry, merit goods, collective action issues, and free riding. Furthermore, training had little impact on reducing the governance challenge arising from information asymmetry.Discussion/conclusionOne of the key solutions was investing in subsidies to increase production and raise awareness of the importance of nutritious foods. With governance problems, there is a need to take them into consideration when planning and expanding biofortification programs.